HISTOMORPHOMETRICAL STUDY OF THE PANCREAS - Dr Shashwati Geeta Deka (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The pancreas is a digestive gland with both endocrine and exocrine functions. The endocrine units called the Islets of Langerhans, contain cells like alpha, beta, etc. and produce hormones like glucagon, insulin-having direct effect on glucose homeostasis. The beta cell failure or insulin resistance can lead to a common serious disease called Diabetes Mellitus.